1987
DOI: 10.1016/s0022-5347(17)43652-4
|View full text |Cite
|
Sign up to set email alerts
|

Difficulties of a Surveillance Study Omitting Retroperitoneal Lymphadenectomy in Clinical Stage I Nonseminomatous Germ Cell Tumors of the Testis

Abstract: Between August 1981 and December 1984, 85 consecutive patients with clinical stage I nonseminomatous germ cell tumors of the testis who were suitable for close observation entered a surveillance study after orchiectomy alone. All patients had unequivocally negative chest x-ray, bipedal lymph-angiography, and computerized tomography of the abdomen and pelvis, and normal levels of alpha-fetoprotein and human chorionic gonadotropin before entering the study. Patients were followed closely for 24 to 64 months (med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
26
2
5

Year Published

1993
1993
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(34 citation statements)
references
References 11 publications
1
26
2
5
Order By: Relevance
“…17,25 Subsequent studies confirmed the importance of the vascular invasion as an independent predictor for relapse in clinical stage I patients. 2,9,10,17,18,25 In contrast to most of the previous studies, we did not find dominant embryonal carcinoma histology to be associated with clinically metastatic disease. Our study evaluated patients of all clinical stages in contrast to most previous studies which included only clinical stage I patients.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…17,25 Subsequent studies confirmed the importance of the vascular invasion as an independent predictor for relapse in clinical stage I patients. 2,9,10,17,18,25 In contrast to most of the previous studies, we did not find dominant embryonal carcinoma histology to be associated with clinically metastatic disease. Our study evaluated patients of all clinical stages in contrast to most previous studies which included only clinical stage I patients.…”
Section: Discussioncontrasting
confidence: 99%
“…We also confirmed that vascular invasion is a significant risk factor for metastasis in nonseminomatous germ cell tumors, which is well documented previously. [2][3][4]9,10,[13][14][15][16][17][18][19] Clinical stage is the most critical step in the management of patients diagnosed with nonseminomatous germ cell tumors. A current challenge is the appropriate management of clinical stage I disease because of the concerns related to the adverse effects of the chemotherapy treatment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations